PENINGKATAN PRODUKTIVITAS PADA LINE ASSEMBLY STOPPER CRASH STOP DENGAN LINE BALANCING - Nurlaila, Qomaratun (Universitas Riau Kepulauan, 2016)
PT. XYZ is manufacturing company, it produces HDD (Hard Disk Drive) components with plastics and rubber material. One of HDD products which used rubber material is Stopper Crash Stop, it’s produced by assembly process. The actual productivity from July – September 2013 indication that have average productivity is less than the standard. The actual productivity is 8,949 Pcs/man/day, but the standard productivity is 10,350 Pcs/man/day. The Main Root Causes, which contribute to productivity of assembly line of Stopper Crash Stop less than the standard are workplace that more than range of operator’s hand, time of machines operation are different, work load are not balanced. And to increase the productivity of assembly line Stopper Crash Stop to achieve the standard done by Kaizen concept in phases and sustainable. 1st kaizen is layout kaizen, re-layout table of vibration machine by make sit position of operator A and operator B is equal. 2nd kaizen is machine kaizen, standardize time of machines operation refers to the fasters one. 3rd kaizen is layout kaizen, optimize wide of table for vibration machine. And 4th kaizen is line balancing kaizen, make work load of operator is balance. The Productivity before kaizen is 8,949 Pcs/man/day and the productivity after kaizen is 12,323 Pcs/man/day (the productivity increases 38%).